Global coherence during discourse production in adults: a review of the literature. Issue 4 (22nd February 2016) - Ellis, Charles; Henderson, Amy; Wright, Heather Harris; Rogalski, Yvonne
Abstract: Background: Global coherence is a metric of expressive language performance that represents the speaker's ability to initiate, plan and maintain a topic of discussion. Studies indicate that disruptions of global coherence can occur during the ageing process and following neurological disease or injury. However, little is known about the specific impact that the ageing process, disease or injury has on global coherence during discourse production. Aims: To review the literature on global coherence in adult populations and assess the impact that age, disease or injury has on global coherence during expressive language tasks. Methods & Procedures: We completed an in‐depth search of Medline and PyschInfo (1990–2014) to identify studies of global coherence in adult populations. We identified studies that included a comparison group and utilized a measure of global coherence during expressive language production among adults. Outcomes & Results: Twenty studies comprised of 692 study participants who met inclusion criteria were identified for the review of the literature. Studies included participants without neurological impairments and individuals with aphasia, traumatic brain injury, dementia, generalized memory impairment and other neurological conditions. Study results indicated global coherence is an expressive language skill that is influenced by the ageing process and neurological disease or injury. Conclusions & Implications: Although evidence indicated that global coherence is negatively influenced by ageing and neurological disease/injury, the heterogeneity of study populations, measurement tools and study designs were limiting factors in determining the exact nature by which these factors impact the skill of global coherence.